transcAnalysis: A Snakemake Pipeline for Differential Expression and Post-transcriptional Modification Analysis - Barros, Pedro H. A.; Silva, Waldeyr M. C.; Brigido, Marcelo M. (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2023: Anais do XVI Simpósio Brasileiro de Bioinformática, 2023)
The transcAnalysis pipeline is a comprehensive tool that allows the analysis of transcriptome data. The pipeline allows for analysis of differential expression, alternative splicing, lncRNA and RNA editing analysis, with a specific focus on A-to-I editing mediated by the ADAR protein. This type of RNA editing is widespread and can significantly affect gene regulation and function. The results from these analyses are integrated, and the events are associated with each gene. The pipeline also integrates results that can help correlate gene expression and post-transcriptional events. This allows for a comprehensive understanding of the functional impact and provides insight into the biological processes and pathways associated with these events. One of the significant advantages of the transcAnalysis pipeline is its ability to perform all these analyses with a single command using the Snakemake package. This feature simplifies the analysis process and makes it accessible to researchers with limited bioinformatics expertise. Its user-friendly ability to perform multiple analyses with a single command make it an ideal choice for researchers looking to analyze transcriptome data.